Effectiveness of occupational Health Education Program upon Workers’ Knowledge Towards Occupational Health Dimensions - Wissam J. Qassim (Iraqi National Journal of Nursing Specialties, 2023)
Objective: To determine the effectiveness of occupational health education program upon the workers’ knowledge towards occupational dimensions. Methodology: A quazi-experimental study was carried out on a purposive ’’non-probability" sample of workers that was selected from the General Company for Batteries Industry at Al-Russafa, and General Company for Cotton Textile at Al-Karkh in Baghdad City. The researcher divided the workers into two equal groups of (30) worker for each one (the study and control group). Results: Analysis of such distribution indicated that almost one third of them was accounted for those who were (27-36) years, married, having (6-10) years of employment, and their Job description was workers. Almost one quarter of them was primary and secondary school graduntes. Half of them. had moderate income and they were equally distributed with respect to their gender. More than one third of them in both groups was accounted for workers who were electrical workers (23.3%). Recommendations: The study recommended that the occupational health oriented education program can be designed, constructed and implemented for workers to increase their awareness toward the impact of work hazards and occupational health.